Unveiling surfaces for advanced materials characterisation with large-area electrochemical jet machining - Speidel, Alistair; Xu, Dongdong; Bisterov, Ivan; Mitchell-Smith, Jonathon; Clare, Adam T (Materials & Design, 2021)
Surface preparation for advanced materials inspection methods like electron backscatter diffraction (EBSD) generally involve laborious and destructive material sectioning and sequential polishing steps, as EBSD is sensitive to both sample topography and microstrain within the near-surface. While new methodologies, like focussed ion beam and femtosecond laser milling are capable of removing material in a layer-by-layer manner to enable the construction of tomographic datasets within the electron microscope, such techniques incur high initial capital cost for slow removal and reconstruction rates. In this study, ambient condition electrochemical slot jets are applied to rapidly etch (e.g. 31 s) large surface areas (e.g. 160 mm 2) at controlled depths (e.g. 20 µm) with no in-process monitoring. Unveiled surfaces are conducive to measurement by EBSD (raw index rates between 75-95%), despite topographic anisotropy arising both from the process and the material. The mechanisms of topography formation during dissolution under the slot jet are analysed and understood. It is proposed that this slot jet method can be applied to create measurement surfaces for analysis with optical-based microstructural measurement routines reliant on topography and directional reflectance, at a significantly lower cost and time intervention than electron beam-based analysis methods.
Keywords: Electrolyte jet machining; electron backscatter diffraction; indexing; materials characterisation; depth profiling; etching